An abietane diterpene and two phenolics from Salvia forskahlei - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1996)
From the roots of Salvia forskahlei a new diterpenoid, forskalinone, two new aromatic compounds, the octanol esters of cis- and trans-4-O-methyl-caffeic acid dimers, were isolated together with the known compounds stigmast-3-one, sitosterol and alpha-amyrin. The structures of the new and the known compounds were established by spectral data. The antimicrobial activity of forskalinone and the dimeric cinnamic acid esters was tested against standard bacterial strains and a yeast, namely Bacillus subtilis ATCC 6633, Staphylococcus aureus 6538P, S. epidermidis ATCC 12228, Proteus mirabilis ATCC 14153, Escherichia coli ATCC 8739, Klebsiella pneumonia ATC 4352, Pseudomonus aeruginosa ATCC 9027, Enterococcus faecalis ATCC 29212, beta-haemolytic Streptococcus and Candida albicans ATCC 10231. Forskalinone showed moderate resistance against S. epidermidis (670 mu g ml(-1)) and slight activity against E. faecalis (168 mu g ml(-1)). trans-4-O-Methyl-caffeic acid dimer octanol ester was inactive while the cis isomer showed a slight activity against C. albicans (156 mu g ml(-1)).
Keywords: Salvia forskahlei; Lamiaceae; forskalinone; octanol esters of cis- and trans-4-O-methyl-caffeic acid dimers antimicrobial activity; CANDELABRUM